Avian Gut function in health and disease [ - Perry, G. C. [ (Graham C.)] (Poultry Science Symposium Series, 2006)
Derived from the 28th Poultry Science Symposium of the World's Poultry Science Association (UK), this book focuses on the current interest of the phasing out of antibiotic use in poultry and covers in-depth interactions between the bird, its diet and ptential pathogens. It also demonstrates. the understanding of the gut health in the 21st century of commercial poultry and flocks and the ultimate safety of poultry product in the human food chain.